Desigualdades sociais e desempenho escolar no Brasil: o que revelam os microdados do ENEM 2021? - Callegario Zacchi, Raquel; Teixeira de Menezes, Daniel; Gomes Ney, Marlon (Latitude, 2025)
The school system is considered one of the most effective instruments of social mobility in Brazil. Would the school really be able to overcome the socioeconomic inequalities presented between different students? Given this discussion that raises major debates within the Sociology of Education, this work sought to understand whether in contemporary times cultural heritage and economic capital still exert a significant influence on school results. From the correlation of microdata from ENEM 2021, the impacts of family income, parental education, school administrative dependence and color/race on student performance were analyzed. The results found that both cultural and economic capital still exert a significant influence on school performance.